Peningkatan Kemampuan Menulis Permulaan Melalui Model Drill and Practice Berbantuan Media Tracing pada Siswa Kelas 1A SD Kanisius Kudus - Veronica Ree’valent Rizang Sulistiyanto; Moh Zulfan Sauqi; Aurelia Cahya Fadhilatul Khalila; Rani Setiawaty (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the effectiveness of the Drill and Practice model assisted by tracing media in improving the beginning writing skills of first-grade students at SD Kanisius Kudus. The study employed a Classroom Action Research (CAR) method conducted in two cycles involving 26 students as research subjects. Data were collected through observation and writing skill tests, while data analysis was performed using a descriptive quantitative approach. The results showed an increase in the average writing ability score from 58.5 in the pre-cycle stage to 82.4 in Cycle II, with learning mastery reaching 88%. The implementation of repetitive practice and visual assistance through tracing media helped improve students’ fine motor coordination, letter formation accuracy, writing neatness, and readability. Variations of tracing media in Cycle II increased students’ engagement and learning motivation during the learning process. This study indicates that the integration of structured practice models with concrete learning media can serve as an alternative instructional strategy to support early literacy development among elementary school students.